2011
DOI: 10.5194/acpd-11-8173-2011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Peroxyacetyl nitrate (PAN) and peroxypropionyl nitrate (PPN) in urban and suburban atmospheres of Beijing, China

Abstract: Peroxyacetyl nitrate (PAN) and peroxypropionyl nitrate (PPN) were measured sequentially in situ by an online gas-phase chromatograph with electron capture detector at urban (Peking University, PKU) and suburban (Yufa, A town in the south of Beijing) sites in Beijing during the photochemical season in 2006. Maximum and average values of PAN were 11.22 ppbv and 1.95 ppbv at PKU during 15 to 27 August, and maximum and average values of PPN were 2.51 ppbv and 0.41 ppbv at Yufa during 2 to 12 September. Average mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 62 publications
3
17
0
Order By: Relevance
“…The ΔO 3 /ΔPAN values obtained by this study in the summer months were 9.92-18.0, which were close to the value of 18.87 reported by Zhang et al (2011) in August 2006 in Beijing, but were generally lower than the values reported in other cities (e.g. 24.3 reported at an urban site of Ontario by Shepson et al, 1992), in forest regions (e.g., 38.2-81.9 reported by Pippin et al, 2001), and at rural sites (e.g.…”
Section: Correlation Between Pan and Osupporting
confidence: 89%
See 2 more Smart Citations
“…The ΔO 3 /ΔPAN values obtained by this study in the summer months were 9.92-18.0, which were close to the value of 18.87 reported by Zhang et al (2011) in August 2006 in Beijing, but were generally lower than the values reported in other cities (e.g. 24.3 reported at an urban site of Ontario by Shepson et al, 1992), in forest regions (e.g., 38.2-81.9 reported by Pippin et al, 2001), and at rural sites (e.g.…”
Section: Correlation Between Pan and Osupporting
confidence: 89%
“…PAN, as the most abundant species among PANs, has been recognized as lachrymators (Altshuller, 1978), mutagens (Shepson et al, 1986), and phytotoxins (Sun and Huang, 1995;Taylor, 1969). PPN as the second largest species among PANs, its atmospheric concentration usually accounts for 4%-20% of PAN (Grosjean et al, 2001(Grosjean et al, , 2002Lee et al, 2008;Zhang et al, 2011), and it is four times phytotoxic (Kleindienst et al, 1990) and five times eye-irritant than that of PAN (Altshuller, 1978). Furthermore, PAN and some of its analogues have been found to 10-50 times toxic to the plant than that of O 3 Marley, 2001a, 2001b;Taylor, 1969).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidants can kill plant cells, causing leaves to develop brown spots or drop off the plant, reduce plant growth, and make plants more susceptible to damage from other causes. Oxidants such as ozone can also corrode and destroy many materials such as rubber, nylon, fabric, and paint [3].…”
Section: Smog Typesmentioning
confidence: 99%
“…As thermal decomposition is a major PAN sink in the troposphere (Beine et al, 1997;Jacob, 2000;Kenley and Hendry, 1982;Talukdar et al, 1995), the lifetime of PAN depends on temperature. For example, the PAN lifetime is ∼ 5 years at −26 • C and 1 h at 20 • C (Fischer et al, 2010;Zhang et al, 2011). At high altitudes above ∼ 7 km, photolysis becomes the most important loss process for PAN (Talukdar et al, 1995).…”
Section: Introductionmentioning
confidence: 99%